1987
DOI: 10.1111/j.1432-1033.1987.tb13545.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the ontogeny of rat liver metallothionein mRNA by zinc

Abstract: To investigate the role of metals in the regulation of the ontogenic expression of rat liver metallothionein (MT) mRNA, the concentrations of zinc, MT and MT mRNA were determined in livers of fetal and newborn rats from dams whch were fed with a control or zinc-deficient or copper-deficient or iron-deficient diet from day 12 of gestation. The liver samples were analyzed for MT-mRNA levels using a mouse MT-I cRNA probe. Although the newborn hepatic levels of each metal (zinc or copper or iron) was specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…As addressed above, metallothioneins (MTs) are also considered to act as ROS scavengers and Zn deficiency caused an almost complete down-regulation of the MT-I mRNA in rat liver (Andrews et al, 1987;tom Dieck et al, 2003) that in turn could again increase the hepatic ROS burden. That gene expression of metallothioneins is not only dependent on the Zn status but also on oxidative stress has been established (Dalton et al, 1996;) and one factor that links ROS status and MT expression could be the metal transcription factor 1.…”
Section: From Fatty Acids To Oxidative Stressmentioning
confidence: 99%
“…As addressed above, metallothioneins (MTs) are also considered to act as ROS scavengers and Zn deficiency caused an almost complete down-regulation of the MT-I mRNA in rat liver (Andrews et al, 1987;tom Dieck et al, 2003) that in turn could again increase the hepatic ROS burden. That gene expression of metallothioneins is not only dependent on the Zn status but also on oxidative stress has been established (Dalton et al, 1996;) and one factor that links ROS status and MT expression could be the metal transcription factor 1.…”
Section: From Fatty Acids To Oxidative Stressmentioning
confidence: 99%
“…In this sense, they help protect cells and tissues against heavy metal toxicity, facilitate the exchange of metals functioning as anti-oxidants in tissues, as well as protecting the cell against hydroxyl free radicals, which can cause an oxidative stress induced apoptosis (87;88). It has been suggested that MT play an important role in Zn-induced cell proliferation and differentiation (89), since they are over expressed in proliferating tissues, such as regenerating and developing rat livers, and certain types oftumors (90)(91)(92)(93). MT also play a role in metal exchange with Zn dependant enzymes, such as carbonic anhydrase (CA), a zinc metalloenzyme that catalyzes the reversible conversion between carbon dioxide and the bicarbonate ion, tlrrough the hydration of carbon dioxide (C02) (94)(95)(96).…”
Section: Ilmentioning
confidence: 99%
“…Thus the protein may be serving as a source of zinc for metabolism in the foetal liver and a protective role in the neonate. Andrews et al [14] reported, however, that in zinc-deficient rats the concentration of hepatic metallothionein mRNA was reduced in foetal and neonatal rats suggesting that in both foetus and neonate metallothionein may be primarily protecting the liver from zinc accumulation. This result is consistent with our suggestion that zinc is the most probable inducer in the neonates [Ill; however, it differs from our conclusions and those of Quaife and Palmiter [12] concerning the regulation of metallothionein genes in the late foetal period.…”
mentioning
confidence: 99%